Gender Prevalence and Management of Small Bowel Tuberculosis at Tertiary Care Hospital Nawabshah - Inayat Ali Zardari, Altaf Hussain Ghumro, Zulfiqar Ali Imtiaz Memon, Imtiaz Ali Soomro, Sadia Ayoub, Mashooq Ali Khowaja, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Abdominal tuberculosis has higher incidence particularly in developing countries. The challenge to Surgeon is to diagnose it as its presentation is very vague and diagnostic tools are dubious.1 Biochemical analysis helps a little bit in this regard. The abdominal tuberculosis which is not so commonly seen as pulmonary TB can be a source of significant morbidity and mortality and is usually diagnosed as late due to its non specific clinical presentation. About 15 to 25% of cases with abdominal tuberculosis here concomitant pulmonary TB.2 Any part of GIT can be affected but it is usually small bowel and sometimes a colon which is affected barium study has some role in diagnosing the ileal tuberculosis and then is on laparoscopic examination.3 Patients and Methods: This is a cross sectional study conducted at People Medical College Hospital Nawabshah. It was conducted in Surgical Unit 1 from January 2019 to December 2021. All the patients admitted in the ward came through OPD or through emergency. History was taken and proper examination of abdomen apart from systemic examination was done. Routine investigations were done. specific investigations like Liver function test (LFT) and serum electrolytes were done. Radiological investigations like ultrasound and x ray chest abdomen in erect and supine posture were done. Diagnosis was made and surgical intervention was done. Results: Total 30 patients were included in this study. Age of patients was between 20-50 years. 9(30%) patients aged between 20-3- years. 10 (33.3%) were of age between 31-40 years and 11 were aged between 41-50 years. Higher prevalence was in 4th and 5th decade of life. Patients with acute emergency were treated by Exploratory Laparotomy. Per operative findings showed stricture in 14 (47%) patients that were treated with resection and end to end anstomosis. 13 (43%) patients had single as well as multiple perforations of more than 4-5 cm in sizes with contamination of contents in abdominal cavity. Covering ileostomy was made in these patients. 3 (10%) patients’ perforations were of .5 to 1 cm with lesser contamination of abdominal cavity. Primary repair was made in these patients. Conclusion: It is concluded that Higher prevalence was in 4th and 5th decade of life. Its prevalence in female is higher as compared to male. .Majority of the patients with Abdominal Tb were treated by resection and end to end anastomisis. Keywords: Prevalence , Gender, Abdominal Tuberculosis, Resection, Anastomosis.